The genetic and economic gains from forest tree breeding programmes in Scandinavia and Finland. Issue 4 (19th May 2017) - Jansson, Gunnar; Hansen, Jon Kehlet; Haapanen, Matti; Kvaalen, Harald; Steffenrem, Arne
ABSTRACT: Plantations of genetically improved forest trees are critical for economic sustainability in forestry. This review summarizes gains in objective traits and the resulting economic impact of tree breeding programmes in Scandinavia and Finland. Genetic improvement of forest trees in these countries began in the late 1940s, when the first phenotypically superior plus-trees were selected from natural environments. The main findings from this review are that (i) tree breeding can increase volume growth in the range 10–25%, and (ii) the bare land value associated with genetically improved trees gives a better return on investment and a shorter rotation period compared to the unimproved forests. As some Nordic countries are quite dependent on the forest industry, breeding programmes that have resulted in economic gains have been beneficial for society. Growth and wood quality traits are often adversely correlated, and the weighting of traits from an economic perspective could provide an index for determining maximum profit from breeding. Tree breeding faces an array of challenges in the future, such as changes in silviculture, climate, new pests and diseases, and demand for wood-based products.